Highly Active Anti-retroviral Therapy Associated Hepatotoxicity: Case Report and Discussion - Gali, Sai Deepak; Pemmasani, Deepishka; Setty, Durga Prasad Thammi (Indian Journal of Pharmacy Practice)
Anti-retroviral Drugs (ARV) drugs are always given in combination of two or three drugs like Tenofovir, Lamivudine, Efavirenz and is often referred as HAART therapy. Though it has potential to reduce the disease progression, it is often associated with adverse drug reactions like hepatotoxicity which has been the concern till date. We present here a case of 42-year-old patient who developed hepatotoxicity induced by ARV drugs with apparent risk factors of female gender and higher CD4 count. This case stresses the need for careful evaluation, regular monitoring and prompt omission of drug on suspicion of hepatotoxicity in reducing the mortality and morbidity in HIV infected patients.
Keywords: Antiretroviral - therapy; Hepatotoxicity; Adverse drug reaction; HIV; HAART.